Formation and Development Trends of the Green Economy in Uzbekistan (MMIT Proceedings, 2026)
This paper examines the formation and development of the green economy in the context of global environmental challenges. It analyzes transformation processes in marketing, management, finance, and logistics under the influence of green technologies. Special attention is given to resource-saving solutions and sustainable development principles. The study includes a case analysis of Uzbekistan, highlighting national strategies, renewable energy projects, and green investments. Key trends and future prospects of green economy development are identified.
Keywords: green economy; sustainability; ESG; resource efficiency; Uzbekistan